I maailmasõja teenetemärgid eesti mehe rinnas. Ordenid ja nende kandmine [World War I decorations worn by Estonian men. Orders and the way they were worn] - Lõhmus, Leho (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2015)
Estonian soldiers and officers in old photographs often wear all kinds of decorations and not all of them are of Estonian origin. They reflect the entire Estonian history in its complexity and controversy. Estonian men usually emerged from World War I wearing the decorations and medals of Imperial Russia and the badges of regiments and military schools. From 1919, the Republic of Estonia tried to regulate and restrict their use with various types of legislation. Therefore, only decorations awarded for military services were allowed on military uniforms. Estonians also received some decorations from the other member states of Allied Powers. There were no special regulations regarding their use. Estonian citizens, mainly of Baltic German origin, had also been awarded military decorations by Central Powers, primarily Germany. The constitutions of 1920 and 1933 prohibited Estonian citizens from accepting decorations from foreign countries. However, this requirement was constantly violated until 1936, when the Decorations Act was passed. As most World War I decorations had been earned before the irst constitution was passed, the prohibition did not apply to them.